Digital Advertising Impact On Sales Performance Of Gen Z In Indonesia E-Commerce - Wijoyo, Agung (International Journal of Science, Technology & Management, 2025)
This study investigates the impact of digital advertising effectiveness and contextual relevance on sales performance among Generation Z consumers in Indonesia’s e-commerce sector. The research aims to assess how persuasive clarity and message personalization jointly influence purchasing behavior within one of the fastest-growing digital economies in Southeast Asia. A quantitative survey method was employed, targeting 300 Generation Z respondents (aged 18–27) in the Greater Jakarta area who have experienced online advertising and subsequent purchases. Data were collected through structured questionnaires and analyzed using multiple regression with robustness checks to validate the findings. Measurement constructs included advertising effectiveness, advertising relevance, and sales performance, adapted from established marketing scales.The results show that both advertising effectiveness and advertising relevance significantly and positively affect sales performance, jointly explaining 66.5% of the variance in consumer purchase behavior. These findings confirm that personalized, persuasive, and contextually relevant digital ads are key drivers of Generation Z’s purchasing decisions.The study is limited to respondents from the Greater Jakarta area, which may affect the generalizability of results to other regions or age cohorts. Future research should examine moderating factors such as platform type, consumer trust, and ad fatigue, and extend the model to cross-country comparisons.For marketers and e-commerce firms, the study highlights the need to integrate persuasive ad design with contextual personalization. Effective strategies include leveraging influencer credibility, employing real-time analytics, and developing content that resonates with Gen Z’s lifestyle and values to maximize engagement and conversion.This research contributes to marketing theory by extending the AIDA model and the Theory of Planned Behavior to the context of Southeast Asian digital commerce. It provides novel insights into the combined role of advertising effectiveness and relevance, a dimension that remains underexplored in emerging markets, and offers actionable implications for data-driven, consumer-centered advertising strategies.